Corrosion Resistance of 317L Stainless Steel in Simulated Marine Environment - ZHAO Ye, HE Zhuang, SHI Weng - long, WU Qing - hua, CHEN Yu - yang, LUO Yao, HUANG Ying - ying, LIU Chang, LI Yu - chun (Cailiao Baohu, 2021)
317L stainless steel has been widely used in the marine environment because of its excellent corrosion resistance, but there is still little research on its corrosion behavior. In this paper, the corrosion behavior of 317L stainless steel in the marine atmosphere and seawater was studied systematically through simulating sea salt aerosol environment and carrying coupon test and seawater immersion experiments with the means of corrosion weight loss method, resistance probe, polarization curves, electrochemical impedance spectroscopy (EIS), XRD， metallographic microscope and other methods. Results showed that with the passage of time, the corrosion rate of stainless steel first accelerated then slowed down, and finally stabilized. Generally, the corrosion rate was not too large; the corrosion rate increased with the increase of atomization concentration, but there was no linear relationship between them; with the increase of temperature, the resistance and charge transfer resistance of the passive film decreased gradually, the protective effect of the passive film on the substrate decreased, and the corrosion rate increased.